THE NEED OF A STRUCTURAL CHANGE IN THE TRIBUTARY SYSTEM - Trujillo Meza, Julio César (2009)
The change of the Tributary (Tax) National System is today a need starting from the Public Budget that contains the income of Public Treasure and therefore the tributary (tax) income of any nature. The need of an integral change of the Tributary (Tax) Regime allowing to include other taxes as the Tax to the Personal Patrimony and the Tax to the Managerial Patrimony eliminating the no-technical taxes and extending the contributors’ base with a strong fight against the informality and the tributary (tax) evasion (this under the responsibility of Sunat) and by this avoiding the fall of collection generated originated by the financial international crisis.